Effect of Postoperative Ketorolac Administration on Bone Healing in Ankle Fracture Surgery. (October 2018) - McDonald, Elizabeth; Winters, Brian; Nicholson, Kristen; Shakked, Rachel; Raikin, Steven; Pedowitz, David I.; Daniel, Joseph N.
Background: In an effort to minimize narcotic analgesia and its potential side effects, anti-inflammatory agents offer great potential provided they do not interfere with bone healing. The safety of ketorolac administration after foot and ankle surgery has not been well defined in the current literature. The purpose of this study was to report clinical healing and radiographic outcomes for patients treated with a perioperative ketorolac regimen after open reduction and internal fixation (ORIF) of ankle fractures. Methods: A retrospective review was performed on all patients that received perioperative ketorolac at the time of lateral malleolar, bimalleolar, and trimalleolar ankle ORIF by a single surgeon between 2010 and 2016 with minimum 4 months follow-up. Patients received 20 tablets of 10 mg ketorolac Q6 hours. Radiographs were evaluated independently by 2 blinded fellowship-trained orthopedic foot and ankle surgeons to assess for radiographic healing. A total of 281 patients were included, with a median age of 51 years and 138 males (47%). Statistical analysis consisted of a linear mixed-effects regression. Results: In all, 265/281 (94%) were clinically healed within 12 weeks and 261/281 (92%) were radiographically healed within 12 weeks. Within the group of patients that did not heal within 12 weeks, mean time to clinical healing was 16.9 weeks (range = 14-25 weeks), and mean time to radiographic healing was 17.1 weeks (range = 14-25 weeks). In patients taking ketorolac, there were no cases of nonunion in our series (n = 281) and no significant difference found between fracture patterns and healing or complications ( P = .500). Conclusions: Perioperative ketorolac use was associated with a high rate of fracture union by 12 weeks. This is the first study to examine the effect of ketorolac on radiographic time to union of ankle fractures. Additional studies are necessary to determine whether ketorolac helps reduce opioid consumption and improve pain following ORIF of ankle fractures. Level of Evidence: Level IV, case series.